Examining the Sustainable Urban Environments - Sel, Berna Dikcinar; Celebioglu, Banu; Ozdemir, Olcay Cetiner (EUROPEAN CENTER SUSTAINABLE DEVELOPMENT, 2015)
Cultural properties, as they narrate the design, art and architectural mentality of the entire periods that they went through from the date they were built until today, are museum-quality buildings that document the social and cultural status. The Harran Houses in the Harran city are among this cultural wealth. The typical conic domed houses date back to 150-200 years from today that are in Harran city which was registered as an archaeological and urban conservation area in 1979 and safeguarded. Within the scope of sustainability of these kinds of settlements to be transferred to the future generations; the importance of achievement of the effective contribution of the ruling authorities, users, local residents and visitors to the recommendations that set forth during the study, importance of development and keeping them alive can be understood. In the study, the touristic purposed usage is recommended for the Harran houses; evaluating the current structural status and environmental requirements of the houses through the data obtained during the Harran 2014 workshop. Evaluation of sustainability of the cultural heritage in architecture from a tourism point of view by discussing sustainability is being transferred together with the distinctive characteristics and the design approaches of the functions.
Keywords: Sustainability; Historical City Centers; Architectural structures; Environmental Sciences & Ecology